Bioacústica do golfinho-comum-de-bico-curto delphinus delphis no Atlântico Sul Ocidental - Simonato, Bruna Pagliani (Universidade Federal de Juiz de Fora (UFJF), 2020)
The short-beaked-common-dolphin Delphinus delphis has a characteristic yellowish lateral color and gray flank and is found in tropical and temperate waters in both coastal and oceanic regions. Individuals are very active and highly communicative. Dolphin repertoires are strongly diversified, comprising whistles and pulsed sounds (clicks and burst sounds). Many studies have been described for D. delphis around the world, although none comprises the slope region of the Western South Atlantic Ocean (WSAO). This study presents the first characterization of the acoustic emissions of short-beaked common dolphin in the WSAO, besides analyze the complexity of whistles and pulsed sounds repertoire as a whole. Intraspecific whistle variations were analyzed considering group size, contours and acoustical parameters. No significant correlation was found between number of whistles and group size (p > 0.322). Upsweep, downsweep and constant were the most frequent contours. A positive association between downsweep contour and group size was detected (p > 0.0403). Whistle frequencies ranged from 1.34 to 35.23 kHz and duration varied from 0.11 to 2.16 seconds. Comparing encounters between years through the Bonferroni method, minimum frequency, duration, and frequency range were significantly different. A C5.0 decision tree indicated that whistles from 2014 and 2015 were correctly classified in 67.0% and 54.0%, respectively. The nMDS grouped the Atlantic and Pacific oceans based on inflection points and duration, further corroborated through PERMANOVA (p = 0.039). Clicks are broadband pulses whose frequencies range from 10 and 150 kHz. The analysis of pulsed sounds took into account echolocation clicks, burst, and short burst sounds. Despite the fact that echolocation clicks are relatively well documented, there is no classification consensus regarding the wide variety of short pulsed signals. K-means analysis resulted in four clusters, whose classification, based on time parameters, exhibited the highest accuracy (87% ...